Experimental modeling of silicate-based geothermal deposits. (September 2017) - Çelik, Aslı; Topçu, Gökhan; Baba, Alper; Akdogan, Yasar; Şentürk, Ufuk; Demir, Mustafa M.
Highlights: Synthetic precipitates were obtained by Reflux and Autoclave apparatuses. Field conditions of Tuzla Geothermal Power Plant were employed in Autoclave system. The precipitates were compared with natural deposits in terms of composition and morphology. The precipitates obtained by Autoclave system are close to the natural deposit. XPS and EPR have been employed for the characterization of the precipitates. Abstract: Scaling by metal silicates represents a major obstacle for geothermal systems. A composition that enables the fabrication of artificial deposits is necessary for the rapid testing of potential inhibitors. In this work, artificial deposits were synthesized by employing experimental conditions similar to those in the Tuzla Geothermal Field in Turkey. Although refluxing enabled the formation of a precipitate that was similar to naturally formed deposits in color and texture, their elemental composition and morphology showed a mismatch. An autoclave enabled the production of a precipitate that more closely resembled naturally formed deposits in color, texture, elemental composition, and structure.